OPTIMALISASI TRADISI KEAGAMAAN DALAM PENGEMBANGAN EKOWISATA RELIGI BERBASIS EKONOMI BIRU UNTUK KEBERLANJUTAN WISATA MAKAM SYEKH ABDURRAHMAN SAPAT DI INDRAGIRI HILIR - Sri Hidayanti; Herdiansyah (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2025)
Religious tourism has great potential in preserving religious traditions and supporting community welfare, but challenges in environmental conservation and community empowerment are still the main obstacles. This research aims to analyze the role of religious traditions in supporting religious ecotourism, identify the application of blue economy principles, and formulate strategies for optimizing the sustainability of Sheikh Abdurrahman Sapas's tomb tourism in Indragiri Hilir. Using a mixed methods approach, the research population consisted of religious tourism stakeholders and local communities. The sample was determined through purposive sampling for qualitative data (15 key informants) and random sampling for quantitative data (150 respondents). The data analysis technique used qualitative analysis and SEM-PLS. The results showed that religious traditions had a significant effect on religious ecotourism (β=0.742), the blue economy had a significant effect (β=0.568), and community empowerment had a significant effect (β=0.623). Religious ecotourism has proven to be a strong mediator towards tourism sustainability (β=0.756). The novelty of the research lies in the integration of religious traditions with the blue economy in the context of religious ecotourism. The implications of the research provide a sustainable tourism development model that synergizes spiritual values, environmental conservation, and community economic empowerment for coastal religious tourism destinations. Wisata religi memiliki potensi besar dalam melestarikan tradisi keagamaan dan mendukung kesejahteraan masyarakat, namun tantangan dalam pelestarian lingkungan dan pemberdayaan masyarakat masih menjadi kendala utama. Penelitian ini bertujuan menganalisis peran tradisi keagamaan dalam mendukung ekowisata religi, mengidentifikasi penerapan prinsip ekonomi biru, dan merumuskan strategi optimalisasi keberlanjutan wisata makam Syekh Abdurrahman Sapat di Indragiri Hilir. Menggunakan pendekatan mixed methods, populasi penelitian terdiri dari pemangku kepentingan wisata religi dan masyarakat lokal. Sampel ditentukan melalui purposive sampling untuk data kualitatif (15 informan kunci) dan random sampling untuk data kuantitatif (150 responden). Teknik analisis data menggunakan analisis kualitatif dan SEM-PLS. Hasil penelitian menunjukkan tradisi keagamaan berpengaruh signifikan terhadap ekowisata religi (β=0,742), ekonomi biru berpengaruh signifikan (β=0,568), dan pemberdayaan masyarakat berpengaruh signifikan (β=0,623). Ekowisata religi terbukti menjadi mediator kuat menuju keberlanjutan pariwisata (β=0,756). Kebaruan penelitian terletak pada integrasi tradisi keagamaan dengan ekonomi biru dalam konteks ekowisata religi. Implikasi penelitian memberikan model pengembangan pariwisata berkelanjutan yang mensinergikan nilai spiritual, konservasi lingkungan, dan pemberdayaan ekonomi masyarakat untuk destinasi wisata religi pesisir.